A 200-m all-out front-crawl swim modifies competitive swimmers` shoulder joint position sense - Uematsu, A.; Kurita, Y.; Inoue, K.; Okuno, K.; Hortobagyi, T.; Suzuki, S. (International Journal of Sports Medicine, 2015)
We tested the hypothesis that an all-out-effort 200-m front-crawl swim trial affects competitive swimmers` shoulder joint position sense. On Day 1, we measured shoulder joint position sense before and after the swim trial, and on Day 2 before and after 2 min of seated rest. On both days, shoulder joint position sense was measured in the seated position using electromagnetic movement sensors in a position-matching paradigm. An investigator abducted participants` left (reference) shoulder joint in the frontal plane to test angles of 90°, 135°, and 180°. Participants then actively abducted the right (indicator) shoulder joint to match the position of the left, reference arm. After the 200-m all-out front-crawl swim trial, the indicator relative to the reference angle differed by 4.4° toward adduction at the 180° (vertical) testing position (P<0.05). Variation in absolute matching error was 3.2° or 2.2 times greater after swim compared with the no-swim control trial. An all-out 200-m front-crawl swim trial can selectively increase competitive swimmers` shoulder joint position sense error and increase variation in matching error in horizontal arm position.